EFFECT OF PH OF GROWTH MEDIUM ON ANTIBIOSIS AND GROWTH PROMOTION ACTIVITIES OF FLUORESCENT PSEUDOMONADS - SRUJANA, P. V. (The Journal of Research, PJTSAU, 2019)
Fluorescent pseudomonads play an important role in the prevention of plant diseases and promote the plant growth by suppressing pathogenic microorganisms, synthesizing growth stimulating plant hormones and increasing disease resistance (Stephane et al., 2005). They play a dual role both in plant growth promotion and disease control (Basha et al., 2012). Disease control involves direct and indirect mechanisms. Direct antagonism by production of diffusible or volatile antibiotic compounds is considered to be a primary mechanism of biocontrol. Indirectly, the pseudomonad bacteria stimulate defence responses in the plant hosts. They promote plant growth directly by production of growth promoting substances like Indole acetic acid (IAA), gibberillic acid and by making the nutrients in soil available to plants through a mechanism like phosphate solubilization (Bhattacharyya and Ghosh, 2007). Indirect plant growth promotion occurs through elimination of pathogens by production of secondary metabolites such as phenazines, phloroglucinols and cyanides (Gutterson et al., 1986; Yoshihisa et al., 1989;) and other major mechanisms like production of siderophores, which can form complexes with iron and make it unavailable to plant pathogens (Manwar et al., 2000).Their efficacy in plant growth promotion and in their biocontrol potential found to vary based on physico-chemical properties of soils like soil type, salinity, texture, pH, temperature and moisture and other (Sangeetha et al., 2011 and Loper et al., 1985). The promising P. fluorescens isolates which were found to suppress Sclerotium rolfsii mycelial growth in vitro by dual culture assay were evaluated for understanding the influence of pH of growth media on their plant growth promotion and antagonistic potential against S. rolfsii and the results are presented in this paper.